Health risks from multiroute exposure of potentially toxic elements in a coastal community: a probabilistic risk approach in Pangkep Regency, Indonesia. Issue 1 (31st December 2022) - Astuti, Ratna Dwi Puji; Mallongi, Anwar; Choi, Kyungho; Amiruddin, Ridwan; Hatta, Muhammad; Tantrakarnapa, Kraichat; Rauf, Annisa Utami
Abstract: Populations in coastal areas are vulnerable to chronic exposure to potentially toxic elements (PTEs) from aquatic ecosystems. In this study, we estimated the health risks from Cd, Cr, Fe, and Pb exposure in river water, sediments, and edible aquatic biota ( Anadara granosa and Chanos chanos ). Human daily intake was determined by an interview process with 287 respondents that were selected by proportional cluster random sampling. The cumulative probability value for total risk exceeded the acceptable limit value, indicating that adverse health impacts from PTE exposure may occur in the Pangkep coastal population. The sensitivity analysis showed that exposure duration and Cr concentrations are the factors with the greatest influence in a recreational exposure scenario, whereas the frequency of exposure to shellfish and milkfish is the most influential factor for health risks in a residential scenario. Thus, reducing Cr concentrations in river water, restricting swimming duration, and limiting the frequency of shellfish and milkfish consumption are required to mitigate health risks in the future.